How Digital Competence Reduces Technostress - Bartra-Rivero, Karina Raquel (2024)
This research examined the link between digital competencies and technostress among university instructors in remote settings in Peru, with the goal of identifying if improving digital skills could help mitigate technostress. A non-experimental, quantitative methodology was employed, gathering data via standardized surveys such as the DigCompEdu Check-In and RED TIC. The participant group comprised 120 teachers, whose responses were analyzed using logistic regression in SPSS v27. Descriptive findings indicated that 55,6 % of the teachers demonstrated a high level of professional commitment, and 58,9 % showed proficient digital pedagogical skills. Inferential analysis showed a significant correlation between digital competencies and technostress, with a Nagelkerke index of 0,622, suggesting that about 62,2 % of the variation in technostress could be explained by differences in digital competencies. The study concludes that enhancing digital competencies among teachers could substantially reduce their technostress, emphasizing the need to effectively integrate these skills into teaching practices to improve the educational experience in virtual settings.